Telomere Length and Depression Among Ex-Prisoners of War: The Role of Subjective Age. (5th February 2018) - Lahav, Yael; Avidor, Sharon; Stein, Jacob Y; Zhou, Xiao; Solomon, Zahava
Abstract: Objectives: Exposure to captivity increases the risk for multiple disturbances that may intensify during old age. In later phases of life, former-prisoners-of-war (ex-POWs) may suffer from depression as well as from accelerated aging, manifested in older subjective age and leukocyte telomere shortening. The current study assesses the link between these varied facets of increased vulnerability during old age and explores (a) the associations between subjective age and telomere length; (b) the mediating role of changes in subjective age over time within the associations between depression and telomere length. Methods: Eighty-eight ex-POWs were assessed prospectively 30 (T1), 35 (T2), and 45 (T3) years after the 1973 Israeli Yom-Kippur War. Depression was assessed at T1; subjective age was assessed at T2 and T3; and telomere length and control variables were assessed at T3. Results: Older subjective age at T3 was associated with concurrent shorter telomeres, beyond the effect of chronological age. Change in subjective age between T2 and T3 mediated the relations between depression at T1 and shorter telomeres at T3 beyond the effects of control variables. Discussion: Findings suggest that the detrimental ramifications of accelerated subjective age involve premature cellular senesces, and may explain the relation between depression and accelerated aging processes among trauma victims. Hence, clinical interventions may seek to address accelerated subjective age among trauma survivors who suffer from depression.